Arendt, Eichmann and the Politics of the Past - Parvikko, Tuija (Pro et Contra, 2021)
Arendt, Eichmann and the Politics of the Past offers a critical analysis of the original American debate over Hannah Arendt's report of the trial of Adolf Eichmann. First published in 2008, Tuija Parvikko's book discusses both the campaign against Arendt organised by American Zionist organisations and the controversy Arendt's report caused within American Jewish intellectual circles. Parvikko's analysis carefully draws from the historical background of the report, discussing Arendt's early studies of Zionism and her critique of the Jewish state. The volume also gives an account of Eichmann's capture in Argentina and the reception of the report among legal scholars and the world press.;This edition includes a new prologue in which Parvikko reflects on her own account in connection to recent academic discussions on the controversy. The author's analysis also covers contributions that have attempted to follow Arendt's notion of thinking without banisters. With them, Parvikko engages in debate about going beyond Arendt's theoretical reflections on cohabitation, sharing the world, and discussing the new political evils of the present world without pregiven norms and patterns of thought.